RANCANG BANGUN SISTEM INFORMASI REKAM MEDIS PASIEN BERBASIS WEBSITE PADA KLINIK BIDAN YANTI - Diki Susandi; Bena Kartika Risalati (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
A medical record is a file containing records and documents regarding patient identity, examination, treatment, actions and other services that have been provided to patients at health care facilities. The practice of providing services, especially in improving the welfare of mothers and children, is a health service provider. In managing medical records at the Yanti Midwife Clinic, they still use the manual method, so it takes time and energy to process patient medical records for data that is still in paper form so that the required reports cannot be directly provided. The system is built using the PHP programming language and MySQL database. The system design uses UML and uses the waterfall method as a system development method. The results of the study are in the form of a web-based patient medical record information system that can assist in the processing of patient data at the Yanti Midwife Clinic.